Complicated history with huge potential: Israeli-Japanese relations’ development - D. А. Maryasis; E. A. Iakimova (Японские исследования)
From an analysis of Russian, Israeli, Japanese, and various English-language sources, the authors conclude that this paper is one of the few studies on the topic of Japanese-Israeli relations in the field of Oriental studies. In particular, in Russian Oriental studies, this is the first article focusing on Japanese-Israeli relations. The authors aim not only to trace the dynamics of bilateral relations in socio-political and economic aspects but also to identify the reasons for their complex history. The study also explores potential future developments. This goal has shaped the article’s structure. It includes a literature review, an examination of cooperation prerequisites, an analysis of political and economic components, and a conclusion. The study’s analysis of historical factors, primarily the Japanese Empire’s attitude towards Jewry, reveals that no significant obstacles existed before diplomatic relations were established to hinder current bilateral and multilateral interaction. Moreover, Japan’s Prime Minister Abe Shinzō relied on positive past experiences to foster increased contacts between Tokyo and Jerusalem. Economic considerations and dependence on external energy resources have played a crucial role in the political and diplomatic sphere for both states. This has led Japanese authorities to maintain a balanced course in the Middle East. Over time, the significance of this task has grown as Tokyo seeks to enhance its international status, particularly within the UN and its specialized agencies. In the realm of economic cooperation, internal crises and differing economic models have hindered progress for a considerable period. However, the distinctive national economies and entrepreneurial cultures of Japan and Israel now present significant opportunities for collaboration.